Non Malignant Osseous Tumours of Facial Skeleton - Khan, Arif Raza; Khan, Mohib Ullah; Yousaf, Naveed; Rashid, Abdur (Journal of Postgraduate Medical Institute, 2011)
Boney sellings of facial skeleton are commmonly seen in young adolesence. The commonest fibrous lesion is fibrous dysplasia; thourhg benign, may expand to cause disfigurement of face, or may cause nasal obstruction or dental maloclusion or even loss of teath, orbital deformity with displopia and optic nerve compression. Early detection and removal is advisable. Some cases may need repeated removal thus preventing the facila deformity. No lesion has been recoreded to change into malignancy. This article present clinical, radiogeraphic and pathological features fibrous dysplasia / ossifying fibroma and giant cell reperative granuloma, the differential diagnosis is presented and the relevant literature is reviewed.